Highly temporally resolved response to seasonal surface melt of the Zachariae and 79N outlet glaciers in northeast Greenland. Issue 19 (13th October 2017) - Rathmann, N. M.; Hvidberg, C. S.; Solgaard, A. M.; Grinsted, A.; Gudmundsson, G. H.; Langen, P. L.; Nielsen, K. P.; Kusk, A.
Abstract: The seasonal response to surface melting of the Northeast Greenland Ice Stream outlets, Zachariae and 79N, is investigated using new highly temporally resolved surface velocity maps for 2016 combined with numerical modeling. The seasonal speedup at 79N of 0.15 km/yr is suggested to be driven by a decrease in effective basal pressure induced by surface melting, whereas for Zachariae its 0.11 km/yr seasonal speedup correlates equally well with the breakup of its large ice mélange. We investigate the influence 76 km long floating tongue at 79N, finding it provides little resistance and that most of it could be lost without impacting the dynamics of the area. Furthermore, we show that reducing the slipperiness along the tongue‐wall interfaces produces a velocity change spatially inconsistent with the observed seasonal speedup. Finally, we find that subglacial sticky spots such as bedrock bumps play a negligible role in the large‐scale response to a seasonally enhanced basal slipperiness of the region. Plain Language Summary: The Northeast Greenland Ice Stream may potentially contribute significantly to near‐term sea level rise and is one of the lesser studied Greenlandic systems, partly due to its remoteness. We present a new high temporally resolved velocity data set derived from Sentinel 1‐A which allows capturing changes on a seasonal timescale, a feature which only the newest generation satellites now permit. We show how surface melting may be linked to the observed seasonal velocity changes, giving important insights into the possible future (range of) behavior and sensitivity of the ice stream outlets to atmospheric changes. In addition, we present a detailed study of possible moderating factors on the seasonal velocity response. In particular, we find that (i) the large ice mélange in front of the Zachariae outlet might be dampening the outlet's response, (ii) small‐scale subglacial topographical bumps (sticky spots) exert very limited control on the flow, and (iii) the 76 km long floating tongue of the 79N outlet is largely a passive feature, suggesting that most of it (∼80%) could be lost without effecting the outlet's contribution to near‐term sea level rise. This has broad implications for assessing the future mass loss of ice sheets since it points to the importance of studying every major calving event individually. Key Points: The 2016 seasonal velocity speedups of Zachariae and 79N are 14% and 11%, respectively, consistent with elsewhere on Greenland and are likely triggered by enhanced subglacial sliding due to surface melting The 79N speedup is unaffected by subglacial sticky spots and is incompatible with enhanced sliding along the sidewalls confining its floating tongue, whereas for Zachariae the ice mélange at its front might play an important role The 76 km long floating tongue of 79N provides, at most, only little resistance from its innermost part, and the remaining outer ∼56–66 km could be lost without large consequences